Characterization of Spatial and Temporal Variation of Ultrafine Particles in a Highway Tunnel. - Perkins, Jessica. (2017)
Abstract: Exposure to traffic–related air pollution has been linked to increased risks of cardiopulmonary disease, asthma, and reduced lung function. Ultrafine particles (UFP; aerodynamic diameter ≤100 nm) may contribute to these increased health risks. Previous tunnel studies have shown that UFP concentrations are highly elevated in poorly ventilated tunnels compared to open–air mixed roadways; however, little work has been done to characterize the seasonal and temporal variation of UFP in a roadway tunnel. The goals of this work were to characterize UFP and other pollutant concentrations along the length of an urban highway tunnel over the course of one year and more intensely during two wintertime days to analyze seasonal and daily trends. The study was done in the Thomas P. O'Neill Jr. Tunnel on Interstate 93 (I–93; ≥1.5x105 vehicles per day) in Boston, MA. Data was collected by driving the Tufts Air Pollution Lab (TAPL) mdash; which measured particle number concentration (PNC, an indicator of UFP) in the 6 nm to 225 nm size range, as well as CO, NO, NOx, PM2.5, PAH, and black carbon — through the tunnel in each direction on 38 days distributed over one year (Sept 2010 — Sept 2011), and then 45 times in each direction over the course of two days (04:00 — 21:30) in January 2012. PNC was ~8–fold higher in the tunnel than on the highway outside during the 12–month monitoring campaign. In the northbound tunnel, the median PNC (particles/cm3) was 2.5–times higher during the winter than the summer. Similar differences were observed in the southbound lanes. In January 2012, median PNC inside the tunnel was higher in the morning than evening. Results of this study could inform strategies for tunnel ventilation.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Civil Engineering.; Advisor: John Durant.; Committee: John Durant, George Allen, and Mary Davis.; Keywords: Atmospheric sciences, Environmental science, and Atmospheric chemistry.